IMPROVING STUDENTS’ READING COMPREHENSION OF THE TWELFTH GRADE STUDENTS OF SMA NEGERI 1 BATANG KUIS THROUGH GROUP INVESTIGATION METHOD - Sinurat, Torang Maruli; Sari, Anna Stasya Prima; Sembiring, Novalina (Kairos English Language Teaching Journal, 2017)
Reading is not only about pronouncing written words correctly but also comprehending the text.Â It is not surprising that students have difficulties in reading comprehension. For example:Â Students cannot understand and share information of the text. Thus, there must be a methodÂ which can help them read effectively. Group Investigation method can help improve theÂ studentsâ€™ reading comprehension and motivation to read. The objectives of this research are toÂ find out that Group Investigation method improves studentsâ€™ reading comprehension and toÂ describe the studentsâ€™ responses towards learning teaching process of reading comprehensionÂ through the application of Group Investigation method. This research is Classroom ActionÂ Research (CAR) which was conducted by applying Group Investigation method to the twelfthÂ grade students of SMA Negeri 1 Batang Kuis. After six meetings, it could be seen that there isÂ a significant improvement of the studentsâ€™ reading comprehension. The results of the testsÂ showed that the studentsâ€™ mean score in the pretest is 60.25 with 15.62% of the students whoÂ got score > 75, the studentsâ€™ mean score in the formative test is 71.25 with 28.12% of theÂ students who got score > 75, and the studentsâ€™ mean score in the posttest is 78.87 with 71.87%Â of the students who got score > 75. The quantitative data analysis showed that there is aÂ significant mean score increase from pretest to posttest, namely about 56.25%. The qualitativeÂ data analysis showed that the studentsâ€™ responses towards the application of GroupÂ Investigation method in the learning teaching processes of reading comprehension on narrativeÂ texts are very positive. They agree that the application of Group Investigation method couldÂ help them improve their reading comprehension. It is suggested that English teachers applyÂ Group Investigation method as an alternative to improve their studentsâ€™ reading comprehension.